A Study of Women Entrepreneurs in Jaipur, doing e-business with the help of social media platforms - Rathore, Neetu; Pareek, Dr. Ashish (Journal of Contemporary Research in Management (JCRM), 2022)
Technology plays an important role in our lives by supporting us and providing a comfortable living at home, technology equally aids our professional activities at work. Especially during the COVID era, technology kept us in touch with our dear ones away from home and helped us to communicate with the rest of the world. This was possible with the help of social media platforms like Twitter, WhatsApp, Facebook, Instagram, etc. Since then, people from all walks of life have become internet- friendly. In the past couple of years, social media platforms have also supported many businesses in marketing and selling their products as there was no possibility of using physical spaces during COVID times. These social media platforms have emerged as a boon for those small women entrepreneurs who cannot invest a large amount in business and are comfortable doing business from home. The current study examined a few women entrepreneurs in Jaipur who used one or the other social media platforms to start and run their small businesses. The findings suggest that social media with all its pros and cons, is an important tool for these women entrepreneurs to showcase their products and sell them effectively while being at home.